(untitled) (Third Sector Social Economic Review, 2020)
The research aimed to explore secondary education students’ cognitive structures related to migration types. It used a survey research design and sampled 275 students studying at a public secondary education institution. The data were collected using a word association test (WAT) consisting of 7 key concepts. As a result of the research, 7663 response words were produced for the 7 key concepts and 1925 related sentences were formulated. The research found that students’ cognitive structures related to migration types are insufficient. The highest number of response words was matched with the key concept brain drain, while the lowest number was matched with transit migration. Among students’ sentences related to the key concepts, 392 contained scientific knowledge, 873 contained superficial knowledge, and 456 contained misconceptions. Sentences containing scientific knowledge were mainly linked to the key concept brain drain. Sentences without scientific knowledge were mainly associated with the key concept transit migration.